Identifying optimal survey-based algorithms to distinguish diabetes type among adults with diabetes - Nooney, Jennifer G.; Kirkman, M. Sue; Bullard, Kai McKeever; White, Zachary; Meadows, Kristi; Campione, Joanne R.; Mardon, Russ; Rivero, Gonzalo; Benoit, Stephen R.; Pfaff, Emily; Rolka, Deborah; Saydah, Sharon (Journal of clinical & translational endocrinology, 2020)
•U.S. diabetes surveillance based on surveys may not reliably distinguish by type.•We married surveys from adults with a gold standard diagnoses based on EHR data.•Our algorithm uses self-reported type and use of insulin to identify type.•Use of our algorithm with large federal health surveys may improve surveillance. Surveys for U.S. diabetes surveillance do not reliably distinguish between type 1 and type 2 diabetes, potentially obscuring trends in type 1 among adults. To validate survey-based algorithms for distinguishing diabetes type, we linked survey data collected from adult patients with diabetes to a gold standard diabetes type. We collected data through a telephone survey of 771 adults with diabetes receiving care in a large healthcare system in North Carolina. We tested 34 survey classification algorithms utilizing information on respondents’ report of physician-diagnosed diabetes type, age at onset, diabetes drug use, and body mass index. Algorithms were evaluated by calculating type 1 and type 2 sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) relative to a gold standard diagnosis of diabetes type determined through analysis of EHR data and endocrinologist review of selected cases. Algorithms based on self-reported type outperformed those based solely on other data elements. The top-performing algorithm classified as type 1 all respondents who reported type 1 and were prescribed insulin, as “other diabetes type” all respondents who reported “other,” and as type 2 the remaining respondents (type 1 sensitivity 91.6%, type 1 specificity 98.9%, type 1 PPV 82.5%, type 1 NPV 99.5%). This algorithm performed well in most demographic subpopulations. The major federal health surveys should consider including self-reported diabetes type if they do not already, as the gains in the accuracy of typing are substantial compared to classifications based on other data elements. This study provides much-needed guidance on the accuracy of survey-based diabetes typing algorithms.